Prevalence and correlates of internalizing and externalizing mental health problems among in-school adolescents in eastern Ethiopia: a cross-sectional study - Gari Hunduma; Yadeta Dessie; Biftu Geda; Tesfaye Assebe Yadeta; Negussie Deyessa (Scientific Reports, 2024)
Abstract Adolescent’s mental health issues are a major social burden and a significant public health issue, but they have not received enough attention in Ethiopia. Therefore, this study aimed to determine the prevalence and correlates of internalizing and externalizing mental health problems among in-school adolescents in the Harari region, eastern Ethiopia. A cross-sectional study was conducted among 3227 in-school adolescents. Multistage sampling was used to select schools and eligible students to participate in the study. A guided, self-administered strength and difficulty questionnaire measured mental health problems. Data were double-entered, validated, and cleaned using EpiData 3.1 and analyzed using STATA version 17. Ordinal logistic regression analysis was performed to estimate the adjusted odds ratio between mental health problems and their correlates. Statistical significance was set at p-value < 0.05. The magnitudes of mental health problems among in-school adolescents by subscale was 24.17% (95% CI 22.72; 25.67) for internalizing and 11.93% (95% CI 10.85; 13.09) for externalizing problems. A high internalizing problem score was associated with females, rural residents, alcohol users, attending public schools, those bullied at school, and those in the lowest wealth index. Likewise, the likelihood of a high externalizing problem score was high among alcohol users, adolescents whose fathers are uneducated, rural, and bullied at school. The study suggests that mental health problems are prevalent among in-school adolescents in Ethiopia, especially internalizing problems. The study also identifies several risk factors associated with internalizing and externalizing problems, such as wealth index, school types, alcohol use, bullying, and rural residence. These factors may indicate the need for more mental health awareness and support programs for adolescents in Ethiopia. This highlights that schools and communities should prioritize mental health awareness and support programs for adolescents. These programs should be tailored to address the specific needs of the population, such as rural residents, those in the lowest wealth index, and those who have experienced bullying.